+0

# 3h-4k=5 5h+3k=-11

0
117
1

3h-4k=5 5h+3k=-11

how to solve with elimination

Guest Feb 20, 2017
Sort:

#1
+5

Solve the following system:
{3 h - 4 k = 5 | (equation 1)
5 h + 3 k = -11 | (equation 2)
Swap equation 1 with equation 2:
{5 h + 3 k = -11 | (equation 1)
3 h - 4 k = 5 | (equation 2)
Subtract 3/5 × (equation 1) from equation 2:
{5 h + 3 k = -11 | (equation 1)
0 h - (29 k)/5 = 58/5 | (equation 2)
Multiply equation 2 by 5/29:
{5 h + 3 k = -11 | (equation 1)
0 h - k = 2 | (equation 2)
Multiply equation 2 by -1:
{5 h + 3 k = -11 | (equation 1)
0 h+k = -2 | (equation 2)
Subtract 3 × (equation 2) from equation 1:
{5 h+0 k = -5 | (equation 1)
0 h+k = -2 | (equation 2)
Divide equation 1 by 5:
{h+0 k = -1 | (equation 1)
0 h+k = -2 | (equation 2)
Collect results:
Answer: |h = -1           and          k = -2

Guest Feb 20, 2017

### 20 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details